Improving data accuracy: Selecting the best data checking technique. - Barchard, Kimberly A.; Verenikina, Yevgeniya (Computers in Human Behavior, 2013)
Highlights: [•] Data checking is used to correct errors that occur during manual data entry. [•] Double entry is substantially more effective than visual checking and read aloud. [•] VC and RA fail to correct many existing errors and also introduce many errors. [•] After checking, most errors are within the allowable range for the variables. [•] Therefore, histograms are not an adequate substitute for entry-by-entry checking.